The University of the Third Age – Teaching, Integrating and Activating - Palma, Agnieszka (Acta Universitatis Lodziensis. Folia Oeconomica, 2022)
The main purpose of this article is to present and bring closer the educational institution of the University of the Third Age, to draw attention to its educational, integrating, and activating role in the life of older people, as well as to define the challenges it faces in the face of the growing process of aging of society. The demographic changes which are taking place are increasing interest in the subject of older people and the ageing of society, but most of all they are inducing the greatest possible activation of older people by enabling them to have contact with their peers, satisfying their need for self-development, education and, above all, acquiring new skills. Universities of the Third Age provide older people with such opportunities. Their dynamic development in Poland and the positive changes they bring both for senior citizens themselves and local communities overshadow the problems they face in their daily activities.